Peran Koperasi dalam Meninkatkann Perekonomian di Kota Kediri (Studi di Koperasi Mubarok ) (AL MUNAZHZHARAH, 2021)
Cooperatives can be said to be a people's economic institution with a social character and must be developed in order to foster economic democracy. The role of cooperatives that have been successfully developed must be encouraged and improved so that they can increasingly play a major role in economic activity. To strive for this, it must be accompanied by guidance so that cooperative activities and the role of members are increasing, so that the benefits of cooperatives are increasingly enjoyed by their members, so that it will improve the socio-economic life of the community. The development of cooperatives in Indonesia shows that cooperatives first developed among government employees, then in rural areas. Which is finally now widespread in all levels of society such as farmers, laborers/employees, traders, civil servants, fishermen, teachers (ustadz), students and so on. Cooperatives were established with the aim of assisting in meeting the needs of members in particular and society in general. This principle must be implemented by an organization that claims to be a shareholder, providing financial assistance from a portion of its business proceeds to establish and develop small and medium-sized enterprises until the Wahidiyah Struggle's economy develops rapidly.